[Peking opera] ([Singapore] [s.n.], 1999)
A recording of a concert of the Peking Opera in 1999, featuring Annie Chen, performing excerpts from Chinese operas and medleys of Cantonese songs.
Disc 1 (57 min.) -- Disc 2 (50 min.) -- Disc 3 (1 hr., 8 min.)
Title from container.
Keywords: Operas, Chinese -- Excerpts; Songs, Cantonese